Integrasi Pembelajaran Matematika Problem Based Learning dengan Teknologi Informasi dan Komunikasi - Qurohman, M. Taufik; Sungkar, Muchamad Sobri (Desimal: Jurnal Matematika, 2018)
Problem-based learning Metode Pembelajaran that is integrated with information and communication technology is expected to be able to provide solutions to increase attractiveness and problem-solving abilities. The purpose of study optimizes PBL Metode Pembelajaran by applying information and communication technology so that there is an increase in the problem-solving ability of the resulting Metode Pembelajaran. Experiments were carried out to get the best Metode Pembelajaran test with indicators of increasing achievement and problem-solving abilities. This research is a Classroom Action Research there are 4 steps: Planning, Action, Observation, and Reflection. The results study The application of contextual learning in applied mathematics courses 2 are: (1) the results of the distribution of questionnaires of students' interest in learning integrated problem based learning ICT before and after being given a learning treatment Problem-based learning has changed from cycle I which is 22.87% increased to 89 00% in cycle II, (2) Increasing student learning activities, this can seen from the percentage  activity in the first cycle of 64% classified as quite active, and in the second cycle by 76% and classified as active, (3) improving achievement, activity, and interest in student learning. This increase can be seen by the acquisition of the average of students in the first cycle of 66.88 and with student learning completeness of 56%. The average value in cycle II is 78.27 and the student learning completeness is 100%.